Investigation of Computers Audiosystems Analog-to-Digital Converters - Grazulevicius, A.; Grazulevicius, G. (Elektronika ir Elektrotechnika, 2001)
The features of sinusoidal test signal application for measurement of effective number of bits (ENOB) of analog-to-digital converters (ADC) are considered. Is displayed, that for an error of quantization the theoretical ADC of a sinusoidal signal applying an equiprobable distribution law, in ENOB calculations arises a methodical error, which value is more for the ADC with better quality. Is retrieved, that the distribution law of a quantization error at enough large sampling, becomes independent from relation of a signal frequency and frequency of sampling and considerably differs from the equiprobable law. Experimentally is established, that the amplitude responses of ENOB of substantial ADC have dropping character. The possibility of a method of an extrapolation for calculation of ENOB of each particular ADC is indicated at maximum input voltage. Is established, that the falling of an amplitude response is more for the ADC with lower quality.